Faktor-faktor yang mempengaruhi kejayaan usahawan kredit mikro di Negeri Johor - Mohd. Osman, Mohd. Hassan (Faculty of Management and Human Resource Development, 2004)
Critical Success Factor (CSF) is the most important element for firms in existing industry to achieve competitive edge. CSF demonstrates the performance whether an enterprise has been successful and unsuccessful in achieving its target mission and vision formulated before the enterprise was formed. Organisation that are able to indentify and utilised CSF will develop its uniqueness in achieving its competitive edge. This study focused on critical success factors of small businesses that received funding under the micro credit scheme in Johor. A total of 233 small entrepreneurs under the TEKUN micro credit scheme were selected for this study. The research was conducted to determine the critical success factors prevalent among TEKUN entrepreneurs in Johor. The objective of the study is also to explore sectors preferred by most TEKUN entrepreneurs. The study identified key and critical factors that are essential for the success of the entrepreneurs and their firm. Ways to enhanced these factors were also proposed. Data collection methods involved interviews with key informants from YTN and by sending in questionnaires to respondent who were successful in obtaining the second TEKUN credit micro funding. Respondents were selected fromthe area of Mersing, Kota Tinggi, Pontian, Tebrau, Johor Bahru and Gelang Patah. The result of the study indicates that the three major critical factors of TEKUN entrepreneurs were management skills, work specialization and persistency (never give up).